2011
DOI: 10.1007/s12374-011-9159-6
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as an Endogenous Plant Regulatory Signal: Debates and Perspectives

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) exists in plants, although it is commonly known as a neurohormone in animals. Indeed, the melatonin level is very high in some medicinal plants and changes developmental stage specifically, indicating that it plays specific physiological roles. Plant melatonin may play unique roles in plants as well as similar functions in animals. Furthermore, exogenously applied melatonin affects developmental processes during both vegetative and reproductive growth. In this study, cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 62 publications
1
65
0
1
Order By: Relevance
“…In rice plants tryptophan is converted to melatonin via tryptamine but not 5-hydroxytryptophan as in animals in the following process: tryptophan decarboxylase (TDC) converts tryptophan to tryptamine which is catalyzed to serotonin by tryptamine-5-hydroxylase (T5H), next serotonin N-acetyltransferase (AANAT) catalyzes conversion of serotonin to N-acetylserotonin, and this is changes to MEL by N-acetylserotonin O-methyltransferese (ASMT). Genes of TDC, T5H and ASMT have been cloned and expressed in rice while gene of AANAT has not been characterized in plants yet (Kang et al 2009;Park 2011, Park et al 2013a. It is suggested that in plants the pathway of this indoleamine can be more complex than it was thought earlier ).…”
Section: Melatonin In Plantsmentioning
confidence: 99%
See 4 more Smart Citations
“…In rice plants tryptophan is converted to melatonin via tryptamine but not 5-hydroxytryptophan as in animals in the following process: tryptophan decarboxylase (TDC) converts tryptophan to tryptamine which is catalyzed to serotonin by tryptamine-5-hydroxylase (T5H), next serotonin N-acetyltransferase (AANAT) catalyzes conversion of serotonin to N-acetylserotonin, and this is changes to MEL by N-acetylserotonin O-methyltransferese (ASMT). Genes of TDC, T5H and ASMT have been cloned and expressed in rice while gene of AANAT has not been characterized in plants yet (Kang et al 2009;Park 2011, Park et al 2013a. It is suggested that in plants the pathway of this indoleamine can be more complex than it was thought earlier ).…”
Section: Melatonin In Plantsmentioning
confidence: 99%
“…Among many functions which MEL performs in plants, its role as an antioxidant molecule and a growth promoter is most supported by experimental evidence (Paredes et al 2009;Park 2011).…”
Section: Antioxidative Role Of Melmentioning
confidence: 99%
See 3 more Smart Citations